Steel slag as low-cost adsorbent for the removal of phenanthrene and naphthalene - Liyun Yang; Xiaoming Qian; Zhi Wang; Yuan Li; Hao Bai; Hong Li (Adsorption Science & Technology)
This study investigates the removal effectiveness and characteristics of phenanthrene and naphthalene using low-cost steel slag with batch experiments. The adsorption characteristics of steel slag were measured and analysed using X-ray fluorescence, X-ray diffraction, and Fourier transform infrared spectroscopy. The batch experiments investigated the effect of the time gradient, pH, and steel slag dosage gradient on the adsorption of the steel slag. The results show that with time and dosage of steel slag increased, the adsorption capacity of phenanthrene and naphthalene increased and gradually became balanced, but pH had no obvious effect on the adsorption of phenanthrene and naphthalene. The Langmuir isotherm model best describes the phenanthrene and naphthalene removal by the steel slag, which shows the adsorption occurring in a monolayer. The maximum adsorption capacity of the steel slag to phenanthrene and naphthalene is 0.043 and 0.041 mg/g, respectively. A pseudo-first-order kinetic model can better represent the adsorption of phenanthrene and naphthalene by steel slag. The research demonstrates that the steel slag has a certain adsorption capacity for phenanthrene and naphthalene.